Level of empathy among undergraduate nursing students of school of health sciences Universiti Sains Malaysia - Rosly, Siti Masyitah Mohd (Universiti Sains Malaysia, 2016)
Empathy is a complex and multi-dimensional phenomenon. It is the ability to understand the patient’s emotion and situation experience by patients. Thus, this study is aimed to measure the level of empathy among undergraduate nursing students of School of Health Sciences, Universiti Sains Malaysia. A cross-sectional study was conducted and the data were collected from February to March 2016 which the respondents involved were 113 of undergraduate nursing students of School of Health Sciences, Universiti Sains Malaysia. Moreover, a pilot study was conducted by using the Jefferson Scale of Empathy: Health Professions Students version questionnaire. In this study, the data analysis was conducted by using Statistical Package for Social Sciences (SPSS) version 22.0. As the result, all the nursing students was scored moderate level of empathy (mean= 87.59). There were no significant association of gender with level of empathy and no significant different between race, religion, student’s own preference to study nursing and willingness to work as nurse after graduate. There was a significant different between years of studying as the p-value <0.02 and level of empathy as the empathy declined as the year of studying increase. As summary, the finding indicates that the level of empathy among undergraduate nursing students was at moderate level and a further study with quantitative research method should be conducted.